2016
DOI: 10.3389/fpls.2016.01437
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Differentiation of Various Melon Horticultural Groups for Use in GWAS for Fruit Firmness and Construction of a High Resolution Genetic Map

Abstract: Melon (Cucumis melo L.) is a phenotypically diverse eudicot diploid (2n = 2x = 24) has climacteric and non-climacteric morphotypes and show wide variation for fruit firmness, an important trait for transportation and shelf life. We generated 13,789 SNP markers using genotyping-by-sequencing (GBS) and anchored them to chromosomes to understand genome-wide fixation indices (Fst) between various melon morphotypes and genomewide linkage disequilibrium (LD) decay. The FST between accessions of cantalupensis and ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 63 publications
4
42
0
1
Order By: Relevance
“…Our molecular results confirmed the previously observed diversity of these Brazilian accessions, and allowed a more accurate classification of them. PCoA results for the whole melon collection are coherent with the classical clusters obtained in previous genetic diversity studies (Esteras et al ., ; Leida et al ., ; Nimmakayala et al ., ). Brazilian accessions represented most of the species diversity, and three groups could be distinguished: one within ssp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our molecular results confirmed the previously observed diversity of these Brazilian accessions, and allowed a more accurate classification of them. PCoA results for the whole melon collection are coherent with the classical clusters obtained in previous genetic diversity studies (Esteras et al ., ; Leida et al ., ; Nimmakayala et al ., ). Brazilian accessions represented most of the species diversity, and three groups could be distinguished: one within ssp.…”
Section: Discussionmentioning
confidence: 97%
“…In melon, a large collection of SNPs is available in the Melogene database (http://www.melogene.net/) due to several transcriptome sequencing and re‐sequencing projects carried out (González‐Ibeas et al ., ; Blanca et al ., , ). SNPs are excellent markers as they are very polymorphic and have been demonstrated to be effective for the establishment of genetic relationships among melon genotypes in previous studies (Blanca et al ., , ; Esteras et al ., ; Leida et al ., ; Nimmakayala et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…GWAS have been conducted for various traits and have identified a series of genes and molecular mechanisms underlying phenotypic variation. Advanced GWAS has been conducted in mainly model plants and major crops; however, GWAS has also been reported in other plants with considerably less dense SNPs and population, such as apple (Amyotte et al, 2017;Farneti et al, 2017;Lee et al, 2017), beans (Sallam et al, 2016;Zuiderveen et al, 2016), and other vegetables (Nimmakayala et al, 2016;Han et al, 2018;Okada et al, 2019). Such kinds of studies in various plants will be conducted to promote NGS platform and resource collection.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…A similar approach was used by Pavan, et al [104], who performed preliminary GWAS and identified SNP(s)/trait associations for flowering time and seed-related traits in a collection of 72 accessions of Cucumis melo from Apulia. Additional GWAS for fruit firmness were performed in a larger collection of melon from Asia and Western hemisphere [105].…”
Section: Linking Genotype To Phenotypementioning
confidence: 99%